Analisis Struktur dan Strategi Nafkah Rumah Tangga Petani Kangkung Darat (Ipomoea reptans) di Desa Kedungjaya Kecamatan Babelan - Fauzia, Rizka; Abubakar, Abubakar; Azzahra, Fatimah (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Land kale is the leading vegetable crop in Bekasi Regency, but the income from land kale farming has not been able to meet all the household needs of farmers in Kedungjaya Village. This situation requires strategies to manage sources of income in order to increase the household income of land kale farmers. The purpose of this study was to determine the structure of the livelihood and the form of the livelihood strategy carried out by the households of the land kale farmers in Kedungjaya Village in meeting their household's needs. Respondents in this study amounted to 37 farmers who were determined by total sampling. The analysis technique used is financial analysis, normal distribution curve rules, and qualitative descriptive analysis. The results showed that the household income structure of land kale farmers in Kedungjaya Village in the upper income layer consisted of 52.66% of income from the on-farm sector, 15.12% of income from the off-farm sector, and 32.22% from the non-farm sector. Then the middle income layer consists of 65.88% of income from the on-farm sector, 12.60% of income from the off-farm sector, and 21.51% of income from the non-farm sector, and the lower income layer consists of 100% income from the on-farm sector. The livelihood strategy implemented by the land kangkung farming household in Kedungjaya Village includes a dual income pattern and migration.